A Review on Artocarpus altilis (Parkinson) Fosberg (breadfruit) - Mukesh S. Sikarwar, Boey Jia Hui, Kumutha Subramaniam, Bavani Devi Valeisamy, Ling Kar Yean, and Kaveti Balaji (Journal of Applied Pharmaceutical Science, 2014)
Artocarpus altilis (Family: Moraceae) is commonly referred to as breadfruit as it is similar to freshly baked bread. Synonyms of Artocarpus altilis are Artocarpus communis and Artocarpus incisus. Basically Artocarpus species consists of phenolic compounds which include flavonoids, stilbenoids, arylbenzofurons and Jacalin, a lectin. Breadfruit (Artocarpus altilis) is originated from A. camansi Blanco (bread nut) which is native to New Guinea, Moluccas (Indonesia) and the Philippines. Many on-going researches are testing the pharmacological activities of Artocarpus altilis. Some of the researches that are being carried out on this plant includes anti-inflammatory, antioxidant, antifungal, sexual behavior, immunomodulatory effect, antidiabetic effect and antibacterial effect. This review will help to provide detailed information on recent researches done on this plant.
Keywords: Artocarpus altilis,Indonesia,Breadfruit.